2009
DOI: 10.1161/circheartfailure.108.798611
|View full text |Cite
|
Sign up to set email alerts
|

Peak Cardiac Power Output, Measured Noninvasively, Is a Powerful Predictor of Outcome in Chronic Heart Failure

Abstract: Background-The cardiac output (CO) response to exercise and other invasively derived hemodynamic variables has been variably described to provide better prognostication than peak VO 2 in patients with chronic heart failure. Using noninvasive measurements of CO during exercise, we compared the prognostic value of peak CO and cardiac power to peak VO 2 in chronic heart failure patients. Method and Results-One hundred seventy-one consecutive patients with chronic heart failure underwent symptom limited bicycle ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 32 publications
(32 reference statements)
6
101
2
1
Order By: Relevance
“…Advances in technology now permit measurement of cardiac output with inert gas-rebreathing techniques (Appendix 1), and recent studies suggest that cardiac power measurements (eg, peak cardiac outputϫmean arterial pressure) may offer enhanced prognostic information beyond peak V O 2 , but these results need to be confirmed. 108 Statistical models that include peak V O 2 have also been developed 109 but are not yet used clinically and remain a promising area for future research. One such model, the Heart Failure Survival Score, is a multivariable predictive index that was developed from data on 80 clinical characteristics of 268 ambulatory patients with advanced heart failure.…”
Section: Systolic Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in technology now permit measurement of cardiac output with inert gas-rebreathing techniques (Appendix 1), and recent studies suggest that cardiac power measurements (eg, peak cardiac outputϫmean arterial pressure) may offer enhanced prognostic information beyond peak V O 2 , but these results need to be confirmed. 108 Statistical models that include peak V O 2 have also been developed 109 but are not yet used clinically and remain a promising area for future research. One such model, the Heart Failure Survival Score, is a multivariable predictive index that was developed from data on 80 clinical characteristics of 268 ambulatory patients with advanced heart failure.…”
Section: Systolic Dysfunctionmentioning
confidence: 99%
“…Other recent reports have demonstrated that peak cardiac output can be measured noninvasively and provides an independent predictor of outcome that can enhance the prognostic utility of peak V O 2 . 108,242 Other potential applications of exercise cardiac output measures include the identification of hyperdynamic states due to impaired peripheral oxygen extraction. The finding of abnormally high cardiac output relative to V O 2 in certain myopathic and autonomic abnormalities provides a rationale for the use of exercise cardiac output measures in the identification of these conditions (see CPX in Patients With Skeletal Muscle Fiber and Mitochondrial Myopathy).…”
Section: Noninvasive Determination Of Cardiac Outputmentioning
confidence: 99%
“…Studies have demonstrated that noninvasively determined peak CO provides an independent predictor of outcomes that enhances the prognostic utility of peak V ⋅ o 2 . [86][87][88][89][90] More recent reports suggest that noninvasively determined peak cardiac index complements indexes of ventilatory inefficiency and peak V ⋅ o 2 and that combining these markers provides the most powerful stratification of risk. 91,92 Although the Fick and thermodilution methods remain the gold standards for the measurement of CO, 93 several rebreathing methods that use CPX are available.…”
Section: Circulatory Powermentioning
confidence: 99%
“…The ventilatory response to exercise has been demonstrated to yield strong prognostic data. 34 Timing of the anaerobic threshold, measurement of cardiac power now with the advent of noninvasive rebreathing technologies, 35 and percent predicted V O 2 36 are parameters that have been examined. Although additional prognostic information can be gleaned from the exercise test, a wealth of additional clinical and laboratory data collected at the time of transplant evaluation needs to be considered.…”
Section: Patients With Class IV Hf Symptoms Not Inotrope Dependent (mentioning
confidence: 99%